Arabic and Islamic Education through the Themes of the Algerian Newspaper:El-Balagh Eljazayri (1926-1948) Between Reality and Aspirations - benmazouz, ameur (The Algerian Historical Journal, 2026)
In this article, we attempt to highlight the views of the Alawi Sufi Tariq and their stance regarding the reality of Arab and Islamic education in colonial Algeria. We survey the writings of El-Balagh El-Jazayry through its different issues. This newspaper represented the mouthpiece and the defender of Sufism and Sufi Tariqs in the face of reformist attacks. After a careful study of the articles of the newspaper, it has become clear that the state of Arabic and Islamic education in Algeria at that time was a preoccupation for the newspaper’s editors and writers. They frequently dealt with this preoccupation through criticism, analysis, proposals, and encouragement of scholars of the nation in an effort to promote it and ultimately preserve the components of the Algerian nationhood presented mainly in the language and religion of Algerians.